Prophetic Communication: Islam as Knowledge Practice - Muhammad Najmuddin; Muhammad Amri; Andi Aderus (Palakka : Media and Islamic Communication, 2022)
Prophetic Communication is briefly defined as 'Prophetic Communication' or 'Apostolic Communication'. Prophetic communication does not only mean "communication that imitates the 'prophet's ways of communicating'', or 'dakwah' or 'Islamic communication', but goes further than that, namely communication that seeks to imitate prophetic goals. so the writer uses two theoretical frameworks, firstly Kuntowijoyo's prophetic communication, as well as Harun Nasution's in Islamic books in terms of various aspects. This research is based on library research. The data collected consists of verses from the Qur'an and written materials that have been published in the form of books, journals, and magazines as well as from the internet which have direct and indirect links. with this research. This research was also carried out using descriptive-analytical research, namely by describing the form of civil society embodied by the prophet through an Islamic communication approach that adorns religious social life. The results of the study found that the Qur'an is substantially and principally very relevant to the content of prophetic communication, namely a). amar ma'ruf (humanization), such as getting used to cooperative behavior, increasing social welfare, strengthening brotherhood, and maintaining social solidarity, b). nahi munkar (liberation), such as egalitarian-based identity construction, poverty alleviation, child protection, and gender equality, c). al-iman billah (transcendence), such as strengthening the values of faith and piety, repentance as a purification of the soul, and internalizing morals.